Exploring novel QTLs among backcross lines for salinity tolerance in rice - KUMARI, SARITA; SINGH, BALWANT; SINGH, SUMEET KUMAR; SATYA, DHRITI; SINGH, SANGEETA; TRIPATHY, KABITA; GAIKWAD, KISHOR; RAI, VANDNA; SINGH, NAGENDRA KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Wild progenitor species of rice (Oryza rufipogon Griff./ Oryza nivara Sharma et. Shastry) are rich source of genes for both the biotic as well as abiotic stress tolerance. Wild rice accession NKSWR 173 has been identified as highly tolerant to salinity stress at seedling stage and moderately tolerant at reproductive stage after evaluation of more than two hundred wild rice accessions from across India. In a bid to introgress the salt tolerance trait from NKSWR 173 to a high-yielding mega variety of rice IR 64, we screened a segregating BC1 population for identification of suitable lines for making the second backcross using both controlled phenotyping and QTL flanking DNA markers. Four lines, namely SN 32, SN 33, SN 39 and SN 45 were found highly tolerant to salinity at both seedling and reproductive stage and were backcrossed to IR 64 to generate BC2F1 seeds for development of advance introgressed lines. Introgression of novel salinity tolerance genes for both the seedling and reproductive stages in mega variety of rice will be useful in achieving high productivity in salt affected rice areas.